Perang Utang pada Hubungan Kepemilikan Institusional dengan Penjualan Pihak Berelasi. - Ermad M.J; Fathul Khaira; Dhea Adhima Suemdra (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
This study aims to examine the role of debt in moderating the effect of institutional ownership on sales to related parties. This research is a sample study, which includes 300 companies from 706 manufacturing sector companies during the 2017-2020 observation year. The sample was selected with certain criteria techniques. The analytical method used is moderated regression analysis. The results of the study found that institutional ownership has a significant positive effect on sales to related parties. Debt is not able to moderate the effect of institutional ownership on sales to related parties.